2021
DOI: 10.3389/fncel.2021.668230
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Adaptation and Laminar Processing of the Oddball Paradigm in the Primary Visual Cortex of Fmr1 KO Mouse

Abstract: Both adaptation and novelty detection are an integral part of sensory processing. Recent animal oddball studies have advanced our understanding of circuitry underlying contextual processing in early sensory areas. However, it is unclear how adaptation and mismatch (MM) responses depend on the tuning properties of neurons and their laminar position. Furthermore, given that reduced habituation and sensory overload are among the hallmarks of altered sensory perception in autism, we investigated how oddball proces… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…However, He and colleagues did find a pronounced deficit in neuronal adaption to repetitive stimulation in FMR1 KO animals, suggesting that tactile hypersensitivity may be driven in part by impaired habituation to sensory input. Similar habituation deficits have been observed in the auditory (Lovelace et al, 2016) and visual (Pak et al, 2021) domains of FMR1 KO mice as well. Interestingly, auditory habituation measured behaviorally using ASR has been shown to depend on intact BK channel function (Typlt et al, 2013).…”
Section: Sensory Hypersensitivity In Fxssupporting
confidence: 80%
“…However, He and colleagues did find a pronounced deficit in neuronal adaption to repetitive stimulation in FMR1 KO animals, suggesting that tactile hypersensitivity may be driven in part by impaired habituation to sensory input. Similar habituation deficits have been observed in the auditory (Lovelace et al, 2016) and visual (Pak et al, 2021) domains of FMR1 KO mice as well. Interestingly, auditory habituation measured behaviorally using ASR has been shown to depend on intact BK channel function (Typlt et al, 2013).…”
Section: Sensory Hypersensitivity In Fxssupporting
confidence: 80%
“…While calcium imaging provides the possibility for highly parallel recordings, its temporal resolution limits the use of comparably fast SOAs in continuous sequences as in the present study. In the visual cortex V1 in the mouse, multiple studies reported responses to sequence violations [e.g., ( 50 52 )], as well as in the somatosensory system ( 53 ). In the auditory system, virtually no, if any, studies have directly looked for omission responses at the cellular level, or have not directly reported them ( 7 , 8 , 13 , 34 , 54 , 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…[e.g., (50)(51)(52)], as well as in the somatosensory system (53). In the auditory system, virtually no, if any, studies have directly looked for omission responses at the cellular level, or have not directly reported them (7,8,13,34,54,55).…”
Section: Relation To Previous Studiesmentioning
confidence: 99%
“…These electrodes have relatively high translational value because of their similarity to epidermal clinical recordings; however, they only record global neuronal activity and the spatial resolution of these type of measurements is low as a consequence of volume conduction. Recent studies using laminar probes found various visual processing deficits specifically in the more superficial layers of the cortex (Kissinger et al, 2020; Pak et al, 2021). Because of volume conduction, visual as well as auditory ERPs were also present in the signals of all recording electrodes, but the amplitudes were highest in the electrodes above the corresponding sensory cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Perceptual experience‐induced oscillations in the V1 were reduced (Kissinger et al, 2020). In an oddball paradigm, KO mice showed similar levels of stimulus‐specific adaptation but stronger mismatch responses (Pak et al, 2021).…”
Section: Introductionmentioning
confidence: 99%